“Twirling an Edge”: Occupational Rituals, Verbal Art and the English Market Trader - Ashton, John (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 1992)
The ritualistic nature of communication and work techniques in many occupational settings is often overlooked. The art of “pitching” is a distinctive, traditional approach to merchandising employed by English market traders that has gone largely unnoticed in folkloristic literature. The stable, recurrent and recognizable component of this occupational ritual and verbal art is the consistent use by its practitioners of a unique marketing strategy. The manipulation of verbal formulas, gesture, costume and merchandise in performance constitute elements of variability within the tradition. This paper examines the principal features of a neglected ritual of English folklore.